Strategi Pemanfataan Teknologi dan Informasi dalam Pembelajaran Guna Mempersiapkan Pelajar Berkarakter di Era Society 5.0 - Indra Lesmana; Mustiningsih Mustiningsih; Luthfia Amanda Sari; Arumia Fairuz Husna; Firda Fitrotul Unsa; Ahmad Furqon Akhbar (Proceedings Series of Educational Studies, 2023)
Abstract: Not over the polemic in the era of the industrial revolution 4.0, now all people in the world are shocked by the idea of a new idea, namely the era of society 5.0. A time that requires humans to be adaptive and creative with fast and appropriate technology. However, to achieve this condition, there needs to be a massive effort from all education actors and direct involvement from parents to create quality graduates who are competent and proficient with technology. This study aims to explain about, (1) the challenges of utilizing technology and information for teachers with SWOT analysis in an effort to prepare students with character , (2) the solutions provided to overcome the challenges of utilizing technology and information in an effort to prepare students with character. This research method uses a qualitative descriptive approach. The data collection technique used in this study was a literature review. The result of this study is that teachers do not maximize the use of technology, especially applications of learning service providers. Online learning activities are only limited to using the whatsapps application. The solution to prepare students with character is to provide varied tasks as well as assistance and control from parents regarding the use of technology.Keywords: learning, character education, information technology, era society 5.0Abstrak: Belum usai polemik diera revolusi industri 4.0 kini seluruh masyarakat di dunia digemparkan dengan ide gagasan baru yakni era society 5.0. Masa yang menuntut manusia untuk adaptif serta kreatif dengan adanya teknologi cepat dan tepat guna. Namun, untuk mencapai kondisi tersebut perlu adanya upaya yang masif dari semua pelaku pendidikan dan keterlibatan langsung dari orang tua guna menciptakan mutu lulusan yang kompeten serta cakap dengan teknologi. Penelitian ini bertujuan untuk menjelaskan mengenai, (1) tantangan pemanfaatan teknologi dan informasi bagi guru dengan analisis SWOT dalam upaya mempersiapkan pelajar berkarakter, (2) solusi yang diberikan untuk mengatasi tantangan pemanfaatan teknologi dan informasi dalam upaya mempersiapkan pelajar berkarakter. Metode penelitian ini menggunakan pendekatan deskriptif kualitatif. Teknik pengumpulan data yang digunakan dalam penelitian ini kajian kepustakaan. Hasil dari penelitian ini adalah guru kurang memaksimalkan pemanfaatan teknologi terutama aplikasiaplikasi penyedia layanan belajar. Kegiatan pembelajaran online hanya terbatas menggunakan aplikasi whatsapps. Solusi untuk mempersiapkan pelajar berkarakter yaitu dengan memberikan tugas bervariatif serta pendampingan dan kontrol dari orang tua mengenai penggunaan teknologi.Kata kunci: pembelajaran, pendidikan karakter, teknologi informasi, era society 5.0